2011
DOI: 10.4236/snl.2011.14018
|View full text |Cite
|
Sign up to set email alerts
|

Poly (Ethylene–Co–Vinyl Acetate)/Clay Nanocomposites: Effect of Clay Nature and Compatibilising Agents on Morphological Thermal and Mechanical Properties

Abstract: A series of nanocomposites based on an ethylene vinyl acetate (EVA) copolymer with two types of inorganic clays was\ud prepared by melt blending and film blowing.The tested clays were Hydrotalcite (a layered double hydroxide) and Dellite\ud 72T (an organo-modified montmorillonite) in different percentage, the exfoliation degree of which has been evaluated\ud in the presence of three types of compatibilisers. The nanocomposite morphology, thermal behaviour and mechanical\ud properties were analysed as function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…This was mainly attributed to the MFI value of polymers. The higher the value of MFI, the higher is the mobility of macromolecules and it is possible to obtain highest the elongation at break results [17]. This result was also observed for the wood-filled thermoplastic composites.…”
Section: Mechanical Propertiessupporting
confidence: 71%
“…This was mainly attributed to the MFI value of polymers. The higher the value of MFI, the higher is the mobility of macromolecules and it is possible to obtain highest the elongation at break results [17]. This result was also observed for the wood-filled thermoplastic composites.…”
Section: Mechanical Propertiessupporting
confidence: 71%
“…The peak broadens, which indicates that there is an increase in the disorder of the clay layers and a better dispersion. When the diffraction peak disappears, it is accepted that the clay layers are completely exfoliated . Peak broadening was largely observed in the EVA composites [EV–NCP( X / Y ) set] obtained with nanopigments, as shown in Figure (a).…”
Section: Resultsmentioning
confidence: 62%
“…In general, the Young's modulus ( E ) values were quite similar, and only the samples with a higher concentration of NC or NCP (5 phr) presented a higher value. Several authors have observed an increase in E values in EVA nanocomposites with increasing concentration of NC, as was observed in this study. We believe that the increase in E was due to an increase in the rigidity provided by the NC, and as the specific surface area was increased, the stress was better transferred through the matrix to the NC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not always possible to obtain a sufficient interaction between the polymer and the organoclay to achieve the desired level of exfoliated structures. Previous studies have indicated that the nature and alkyl-chain length of the modifier affect the structure of nanocomposites [19,20] . The rheological behavior of nanocomposites may reveal information about the relationship of the polymer chain and organoclays structure.…”
Section: Introductionmentioning
confidence: 99%